Book Review of "Critical Inquiries for Social Justice in Mental Health: Relevance for Counseling and Psychotherapy in Canada " - Wada, Kaori; West , Alyssa M. (Canadian Journal of Counselling and Psychotherapy, 2021)
The voices of nearly 40 scholars, activists, and practitioners are brought together in Critical Inquiries for Social Justice in Mental Health. Their diverse contributions are united around a fundamental goal of deconstructing mental health systems to reveal how they produce and sustain social injustices. This review is structured around the three central organizing principles that Morrow and Malcoe weave throughout the book: (a) challenging dominant epistemologies, (b) emphasizing individuals’ resistance to social injustices, and (c) reimagining mental health systems. We offer our reflections about the book’s utility from the perspectives of a professor and a graduate student.